(untitled) (CIPEEX, 2025)
This study refers to a curricular extension proposal aimed at discussing domestic violence against women, developed in the municipality of Rubiataba. The action was structured in three stages: literature review on the subject, planning in collaboration with the school community, and the implementation of a roundtable discussion, held on May 15, 2024, with students from the 1st, 2nd, and 3rd years of high school at a local public school. The objective was to foster critical reflection on the effectiveness of the protective measures established by Law No. 11.340/2006 (Maria da Penha Law) and on the State’s ability to ensure the physical and moral integrity of the victims. The method adopted involved bibliographic research on the historical contextualization of the law, analysis of the cycle of violence, and survey of assault rates against women, articulated with the perceptions shared by the participants during the meeting. The results indicated that, although the Maria da Penha Law represents an essential milestone in confronting gender-based violence, challenges persist regarding its implementation, especially due to the structural limitations of the State and the insufficiency of public protection policies. The discussion enabled the identification of multiple forms of violence suffered by women, physical, psychological, patrimonial, and moral, broadening the students’ understanding of the seriousness and complexity of the problem. It was concluded that the extension activity played a relevant role by integrating academic knowledge and community participation, reinforcing the need for effective public policies and greater social engagement in combating domestic violence.